A Practical Guide to Distributed Scrum - Woodward, Elizabeth; Surdek, Steffan; Ganis, Matthew (IBM Press, 2010)
Succeed with Scrum in Even the Largest, Most Complex Distributed Devel opment Projects Forewords by Ken Schwaber, Scott Ambler, Roman Pichler , and Matthew Wang This is the first comprehensive, practical guide fo r Scrum practitioners working in large-scale distributed environments. Written by three of IBM’s leading Scrum practitioners–in close collab oration with the IBM QSE Scrum Community of more than 1000 members wor ldwide–this book offers specific, actionable guidance for everyone who wants to succeed with Scrum in the enterprise. Readers will follow a journey through the lifecycle of a distributed Scrum project, from env isioning products and setting up teams to preparing for Sprint plannin g and running retrospectives. Each chapter presents a baseline drawn f rom “conventional” Scrum, then discusses additional issues faced by di stributed teams, and presents specific best-practice solutions, altern atives, and tips the authors have identified through hard, empirical e xperience. Using real-world examples, the book demonstrates how to app ly key Scrum practices, such as look-ahead planning in geographically distributed environments. Readers will also gain valuable new insights into the agile management of complex problem and technical domains. C overage includes•  Developing user stories and working with Product Ow ners as a distributed team•  Recognizing and fixing the flaws Scrum ma y reveal in existing processes•  Engaging in more efficient Release an d Sprint planning•  Conducting intense, brief daily Scrum meetings in distributed environments•  Managing cultural and language differences• Resolving dependencies, performing frequent integration, and maintai ning transparency in geographically distributed environments•  Success fully running remote software reviews and demos•  Brainstorming what w orked and what didn’t, to improve future Sprints This book will be an indispensable resource for every team leader, member, product owner, o r manager working with Scrum or other agile methods in any distributed software development organization.